2003
DOI: 10.1063/1.1577824
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced phase transition of metallic SmS thin films by a femtosecond laser

Abstract: Effect of the electrode materials on the resistive switching of Ti4O7 Appl. Phys. Lett. 101, 053502 (2012) Bipolar resistive switching characteristics of Al-doped zinc tin oxide for nonvolatile memory applications Appl. Phys. Lett. 101, 052901 (2012) Orbital symmetry induced conductance switching in a graphene nanoribbon heterojunction with different edge hydrogenations Appl. Phys. Lett. 101, 053101 (2012) Strongly coupled phase transition in ferroelectric/correlated electron oxide heterostructures Appl. Phys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…The samarium chalcogenides have shown pressure-induced transition from the semiconducting to the metallic state [14][15][16][17]. It is also called the black-golden transition; this appears at about 6.5 kbar at room temperature [14,[16][17][18][19][20].…”
Section: Iitheoretical Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The samarium chalcogenides have shown pressure-induced transition from the semiconducting to the metallic state [14][15][16][17]. It is also called the black-golden transition; this appears at about 6.5 kbar at room temperature [14,[16][17][18][19][20].…”
Section: Iitheoretical Calculationmentioning
confidence: 99%
“…It is also called the black-golden transition; this appears at about 6.5 kbar at room temperature [14,[16][17][18][19][20]. The total energy in a crystal is given by…”
Section: Iitheoretical Calculationmentioning
confidence: 99%
“…The results of grazing incidence Xray diffraction and Xray photoelectron analyses revealed that metallic to semiconductorSmS phase transition occurred by the fs laser irradiation. 53),54) Figure 13 shows the reflectance spectra of the asdeposited and fullyirradiated SmS films. This phase transition was ac companied by the significant reflectance change of the film up to 40÷ in the visible region and up to 45÷ in the nearinfrared region.…”
Section: Transparent Galaso Glassceramicsmentioning
confidence: 99%
“…The SmS returns to semiconducting state at lower pressure of about 0.5 kbar [1]. The Band gaps of samarium chalcogenides are 0.15 eV, 0.45eV and 0.65eV respectively at zero pressure [1][2][3][4][5]. The transition is associated with the promotion of a 4f electron in the 5d band, changing the valence from Sm 2+ to Sm …”
Section: Introductionmentioning
confidence: 99%